Upper extremity dvt in oncological patients: analysis of risk factors. Data from the RIETE registry - Monreal, M.; Munoz, F.J.; Rosa, V.; Romero, C.; Roman, P.; Di Micco, P.; Prandoni, P. (Experimental Oncology, 2006)
Aim: The aim of the study is to up date informations on the clinical characteristics and outcome of patients with upper-extremity deep vein thrombosis (DVT) from the Informatised Registry on Venous Thromboembolism (RIETE). Methods: RIETE is an ongoing registry of consecutive patients with symptomatic, objectively confirmed, acute venous thromboembolism. In this analysis the clinical characteristics and 3-month outcome of all cancer patients with upper-extremity DVT were evaluated. Results: Up to February 2006, a total of 14,391 patients with symptomatic, objectively confirmed acute venous thromboembolism had been enrolled in RIETE. Of the 2,945 patients with active cancer 196 (6.7%) had arm DVT: 104 had catheter-associated DVT. Most cancer patients with arm DVT were males, younger than 65, and had a low incidence of additional risk factors or underlying diseases. Twenty of them (10%) had symptomatic pulmonary embolism (PE). Most patients were treated with low-molecular-weigh heparin, both initially (94%) and after discharge (75%). During the 3-month follow-up period 12 patients (6.1%) developed VTE recurrences (PE 6, DVT 6), 8 (4.1%) had major bleeding (fatal in 3), 43 (22%) died. Conclusions: Our data from the RIETE registry show that upper limb DVT is a serious complication in patients with cancer, with a high incidence of recurrences and bleeding complications. Цель: обновить базу данных по клиническим характеристикам и течению заболевания у больных с тромбозом глубоких вен
верхних конечностей (ТГВ) с использованием системы регистра венозного тромбоэмболизма (СРВТ). Методы: СРВТ является
непрерывной системой регистрации больных с симптомами объективно подтвержденной острой венозной тромбоэмболии.
Проанализированы клинические характеристики и течение болезни на протяжении месяцев у больных онкологического профиля
с ТГВ. Результаты: в период декабря 2006 г. были обследованы 14 391 больных с симптоматической объективно подтвержденной
острой венозной тромбоэмболией при помощи системы СРВТ. Из 2945 больных с прогрессирующим течением заболевания
у196 (6,7%) человек выявили ТГВ верхних конечностей: у 104 — ассоциированный с катетером ТГВ. Большинство больных
с ТГВ верхних конечностей — лица мужского пола в возрасте моложе 65 лет и с низкой частотой дополнительных факторов
риска или первичного заболевания. У 20 из них (10%) отмечали симптомы эмболии легочной артерии (ЭЛА). Больные получали
низкомолекулярный гепарин и в начале исследования (94%), и по его окончании (75%). В течение последующих трех месяцев
у12 больных (6,1%) развился рецидив венозной тромбоэмболии (ВТЭ) (ЭЛА – у 6 больных, ТГВ – у 6 больных), у 8 (4,1%)
отмечали кровотечение (3 случая с летальным исходом), 43 (22%) пациента умерли. Выводы: данные СРВТ системы показали,
что ТГВ верхних конечностей является серьезным осложнением у больных, онкологического профиля, сочетающимся с высокой
степенью развития рецидива и осложнений, сопровождающихся кровотечениями.